Legitimation of Commercial Surrogacy in Russia - Dushina, Anastasiya; Kersha, Yuliya; Larkina, Tatyana; Provorova, Daria (Journal of Economic Sociology, 2016)
In modern life commodification has become a widespread phenomenon. A prime example of unique object commodification is commercial motherhood surrogacy motherhood, within which maternity turns from “the women’s social mission” into a service where human life is a final product of monetary transaction. According to Igor Kopytoff, violation of the border between commodities and unique objects leads to the undermining of social order [Kopytoff 2006]. Nevertheless, the existence of commercial surrogacy does not bring disorder, and therefore, the question is: how can this commercial service be functional and legitimate in society? The study is based on the analysis of 14 interviews with staff members of Moscow reproduction clinics and agencies providing the legal support services for surrogate mothers. The authors show that identification of the child’s status, selection of potential parents and surrogate mothers, as well as the regulation of relations between them by staff members, are formed in a way to fit the notion of kinship in accordance with the Euro-American theory of David Schneider [Schneider 1980]. The theory has at its core the idea that kinship relations are primarily determined by common genetic substance and secondarily by social relationships based on specific behavior patterns in the family. This leads to the priority of genetic kin in the creation of kinship ties perception and the decreasing significance of the gestational relationship. Thus, staff members’ recognition of the genetic ties as dominating above all allows for legitimation of commercial surrogacy as a whole and in its organizational aspects through decommodification of the child, who is no longer considered an object of market transaction.